Laser surface treatment of stainless steels - Nur Zuhair Zaharudin (Nanyang Technological University, 2020)
Lasers provide the tools for developing unique methods of treating the surface of materials. With the development of more powerful lasers, surface treatment technology is rapidly growing in the identification of new and improved processing methods. Evaluation and optimization of laser processing methods using analytical modeling, rapid solidification, phase transformation, strengthening mechanism and materials testing can bring potentially cost-effective manufacturing methods or repair of valuable products [1]. Among the various laser surface treatment processes that are available, laser surface hardening and laser shock peening have been chosen for this project. These two laser surface treatment methods were used to treat AISI 420 martensitic stainless steel, which is a widely used commercial tool steel with good corrosion resistant property. This project was done to study the effects of each laser surface treatment method as well as the effect of combining both methods by carrying out each surface treatment, one after the other, on the same specimen. A systematic analysis was carried out to obtain the hardness and microstructure of the treated samples to establish a relationship between the structures and their mechanical properties.